Design and testing of a new energy harvesting device - Muhammad Fharhan Jaffar. (2013)
Vortex induced vibration (VIV) is a natural phenomenon that impacts negatively on many engineering situations. Recently, many studies have been made to explore the feasibility of using this conventionally destructive power and convert it into useful energy. The main objective of the project is to design and develop a test rig to harness energy from VIVs induced from wind. Four cylinders of the same length but of different diameter and mass will be tested in four configurations with different spring stiffness. The report covers the design of the test rig as well as the experiment setup, presents the results, and also investigates individual factors affecting the performance of VIVs. The performance in vortex induced vibration such as the amplitude ratio, frequency ratio and synchronisation region will be investigated in the project. In the experiments conducted, it was found that the largest cylinder of the four produced the best VIV. Despite its low vibration frequency, it produced the largest amplitude and had the widest synchronisation region. On the contrary, the smallest cylinder produced VIV with the smallest amplitude and narrowest synchronisation range but the highest vibration frequency. Lastly, the design of the energy harvesting device which integrates the linear alternator as the generator into the test rig is also discussed for future development.